2012
DOI: 10.1111/acer.12027
|View full text |Cite
|
Sign up to set email alerts
|

Local Changes in Neurosteroid Levels in the Substantia Nigra Reticulata and the Ventral Tegmental Area Alter Chronic Ethanol Withdrawal Severity in Male Withdrawal Seizure‐Prone Mice

Abstract: Background Allopregnanolone (ALLO) is a potent positive modulator of γ-aminobutyric acidA receptors (GABAARs) that affects ethanol withdrawal. Finasteride (FIN), a 5α-reductase inhibitor that blocks the formation of ALLO and other GABAergic neurosteroids, alters ethanol sensitivity. Recently, we found that Withdrawal Seizure-Prone mice from the first genetic replicate (WSP-1) exhibited behavioral tolerance to the anticonvulsant effect of intra-hippocampal ALLO during ethanol withdrawal and that intra-hippocamp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 45 publications
4
9
0
Order By: Relevance
“…Another potential explanation for the lack of genotype difference in chronic withdrawal is that the presence of 5α-reductase-2 in the KO mice compensated for any impact of Srd5a1 deletion on ethanol withdrawal severity. We have found that microinjection of finasteride into discrete brain regions, which would only inhibit Srd5a1 , was required to significantly increase chronic ethanol withdrawal severity (Gililland-Kaufman et al, 2008; Tanchuck et al, 2013), whereas systemic finasteride did not significantly alter chronic ethanol withdrawal severity in male and female C57BL/6J mice (Finn et al, 2004b). Future studies could pharmacologically inhibit the type 2 enzyme in the Srd5a1 mutants or test the double mutants that have been developed (mice lacking Srd5a1 and Srd5a2 ; Mahendroo et al, 2001) and determine the impact on chronic ethanol withdrawal severity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another potential explanation for the lack of genotype difference in chronic withdrawal is that the presence of 5α-reductase-2 in the KO mice compensated for any impact of Srd5a1 deletion on ethanol withdrawal severity. We have found that microinjection of finasteride into discrete brain regions, which would only inhibit Srd5a1 , was required to significantly increase chronic ethanol withdrawal severity (Gililland-Kaufman et al, 2008; Tanchuck et al, 2013), whereas systemic finasteride did not significantly alter chronic ethanol withdrawal severity in male and female C57BL/6J mice (Finn et al, 2004b). Future studies could pharmacologically inhibit the type 2 enzyme in the Srd5a1 mutants or test the double mutants that have been developed (mice lacking Srd5a1 and Srd5a2 ; Mahendroo et al, 2001) and determine the impact on chronic ethanol withdrawal severity.…”
Section: Discussionmentioning
confidence: 97%
“…The withdrawal-induced decrease in endogenous ALLO levels was accompanied by a significant reduction in activity and expression of 5α-reductase and 3α-HSD (Cagetti et al, 2004; Finn et al, 2004a; Tanchuck et al, 2009), and separate studies determined that administration of finasteride increased chronic ethanol withdrawal (Gililland-Kaufman et al, 2008; Tanchuck et al, 2013). These preclinical findings are consistent with results in small cohorts of alcoholic patients in which a decrease in plasma ALLO and THDOC levels corresponded to an increase in the subjective ratings of anxiety and depression during the early withdrawal phase (Romeo et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…GABAergic neurons within the VTA have interconnectivity with cortical and limbic regions (Diana et al., ), and the VTA appears to be sensitive to endogenous modulation of 3 α ,5 α ‐THP levels (Frye and Rhodes, ). Recently, it was shown that microinjection of 3 α ,5 α ‐THP directly into the VTA produced an anticonvulsant effect in air‐exposed WSP mice (Tanchuck et al., ). Following CIE exposure, GABAergic modulation of dopamine VTA neurons was decreased during acute withdrawal (Diana et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, basal levels of 5 neuroactive steroids were lower in WSP-1 versus WSR-1 mice, so a withdrawal-induced decrease in WSP-1 mice may have a greater physiological consequence versus a similar decrease in WSR-1 mice (e.g., 3α,5α- and 3α,5β-androstanediols). Additionally, it should be considered that ethanol withdrawal renders WSP mice (but not WSR) from both genetic replicates tolerant to the anticonvulsant effects of exogenous ALLO administration (e.g., Finn et al, 2006; Gililland-Kaufman et al, 2008; Tanchuck et al, 2013). This behavioral tolerance corresponded to a rightward shift in the ability of ALLO to potentiate GABA-stimulated chloride flux in forebrain microsacs (Finn et al, 2006), consistent with a reduction in GABA A R sensitivity to GABA A R-active neuroactive steroids during ethanol withdrawal in WSP mice.…”
Section: Discussionmentioning
confidence: 99%